2018
DOI: 10.3389/fpls.2018.00652
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Setaria viridis Transformation: Agrobacterium-Mediated to Floral Dip

Abstract: Setaria viridis has many attributes, including small stature and simple growth requirements, that make it attractive as a model species for monocots. Genetic engineering (transformation) methodology is a key prerequisite for adoption of plant species as models. Various transformation approaches have been reported for S. viridis including tissue culture-based and in planta by Agrobacterium tumefaciens infection of floral organs referred to as the floral dip method. The tissue culture-based method utilizes A. tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 39 publications
0
29
1
Order By: Relevance
“…Notably, the overall transformation efficiency reported in this study has been significantly higher than those from previous studies, i.e. 5-15% for the variety A10.1 (Van Eck, 2018; Nguyen et al ., 2020). The difference between the observed transformation efficiencies could be attributed to the S. viridis variety, ME034v, used in this study.…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…Notably, the overall transformation efficiency reported in this study has been significantly higher than those from previous studies, i.e. 5-15% for the variety A10.1 (Van Eck, 2018; Nguyen et al ., 2020). The difference between the observed transformation efficiencies could be attributed to the S. viridis variety, ME034v, used in this study.…”
Section: Resultscontrasting
confidence: 85%
“…Furthermore, the expanding genetic and genomic resources, including diverse germplasm accessions, chemically induced mutant populations, high quality reference genome of the A10.1 variety and the resequenced genomes from more than 600 wild accessions, make it possible to conduct large-scale gene discovery and functional genomics in S. viridis (Bennetzen et al ., 2012; Zhu, Yang and Shyu, 2017; Huang et al ., 2019). Lastly, as another key factor for a successful model plant system, an efficient agrobacterium-mediated transformation method has been reported in S. viridis indicating it is amenable to genetic engineering techniques (Van Eck, 2018; Huang et al ., 2019; Nguyen et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Establishment of the optimum concentration of the selective agent is another critical parameter that requires determination to ensure efficient and reproducible Agrobacterium-mediated transformation of a selected species. The pANIC12A plant expression vector used in this study contains a hygromycin (HPTII) resistance gene, and previous research has reported that HPTII is an effective selectable marker for S. viridis transformation (Martins et al, 2015a;Van Eck, 2018). Here, we show that all assessed hygromycin concentrations (15, 20, 25, and 30 mg/L) reduced the rate of recovery of non-transformed material (callus through to plantlets) during culturing.…”
Section: Discussionmentioning
confidence: 59%
“…Although much progress has been made underlying the molecular mechanism of strawberry fruit ripening using transiently-genetic fruit transformation and stably-genetic transformation systems, in which some limits are existed [1-14, 16, 37]. Notably, it is previously reported that the Agrobacterium-mediated seed transformation may facilitate the entry of Agrobacterium tumefaciens into the seeds to integrating a target gene into the embryo cells [31][32], similar to the pollen-tube mediated genetic transformation method widely used in Arabidopsis thaliana [24,30]. Reference of the seed transformation method [31][32], we rst establish the Agrobacterium-mediated transformation of the germination seeds in diploid strawberry by a series of optimization conditions.…”
Section: Discussionmentioning
confidence: 99%